(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Hypovitaminosis D and Type 2 Diabetes Mellitus (T2DM) are public health concerns that have contributed to multiple adverse health outcomes. Recent studies linked Vitamin D Deficiency (VDD) and Insufficiency (VDI) with glycaemic control and diabetic complications in T2DM. The study assessed the association between vitamin D measured as serum 25hydroxy vitamin D [25(OH)D] level and T2DM at a tertiary care hospital in Chattogram, Bangladesh. Materials and methods: Sixty diagnosed T2DM patients (Case) attending Chittagong Medical College Hospital (CMCH) and 60 non-diabetics, apparently healthy individuals (Controls) were included in this study. Serum vitamin D levels were measured by chemiluminescent immunoassay and were categorized as Vitamin D Sufficiency (VDS) VDI and VDD with levels of ³ 30.0, 20.0–29.9 and <20.0 ng/ml, respectively. Results: The mean age of the T2DM patients was 47.8±8.8 years, with a mean duration of diabetes of 8.9±5.2 years, and 61.7% were male. The mean serum vitamin D levels were 24.3±7.9 and 31.7±7.6 ng/mL, respectively, in T2DM and control group (p<0.001). Taking a cut of 30 ng/ml, 70% of T2DM patients had either VDD or VDI compared to 31.3% of non-diabetic control subjects. In logistic regression analysis, participants with VDD were 7.486 times [Odds ratio (OR) 7.486, 95% confidence interval (CI) 2.78 to 13.80, p<0.001] increase odds of being T2DM. In comparison, those with VDI were 3.45 times [OR 3.45, 95% CI 1.32- to 8.957, p = 0.011)] increased odds of being T2DM. Duration of diabetes inversely correlated with serum 25(OH)D levels in T2DM patients (r=-0.54, p<0.001). Conclusion: VDD is an independent predictor of T2DM. Future prospective interventional research should clarify vitamin D’s crucial therapeutic role in prevention and management of T2DM. JCMCTA 2024 ; 35 (1) : 161-166